The financing system of settlements’ water management reflected by the application period of 2021-2027 (Academic Journal of Internal Affairs, 2020)
Water increasingly appears as a safety deficit in the preference system of the world’s citizens. Even from economical point of view the countries with appropriate water management have considerable potentials. Due to climatic change there is an increasing pressure on Hungary considering available sweet water stocks, and there is an asymmetry of supply and demand in several regions to experience. The more and more extreme weather phenomena take negative effects on water supply. The water supplies, changing temporally and spatially, have considerable negative effects in medium to long-term on environment’s safety and these are even on social level to experience. The helplessness against extremities restrict Hungary’s competitiveness and economic resilience. The water demands aggravate competition for water in several branches of economy, as a power source, while not only the quantity but also the quality of the water stock must be protected. Our settlements are even more helpless and vulnerable against the effects of climatic change and on this area are population and economic activities in majority, and cities are frequently settled on areas more sensible against climatic changes (e.g. on areas exposed to floods, inland waters, droughts). The water systems of cities – including drinking water supply system, wastewater and rainwater removal and clearing system- are particularly endangered, as the climatic change manifests itself in changes of the hydrological cycle (Buzás, 2015). As new elements in the activity-portfolio of the General Directorate of Water Management appear water management and rainwater management of settlements. For us, as an important branch of the Ministry of Interior, it is important to put this topic on the agenda. The elaboration of basic technical, economic and legal frames for water management and rainwater management of settlements is a task of high priority for the Hungarian water management. To the tasks and to general targets belongs a further strengthening of water management, based on real and actual digital basis, suiting to achievements of the target states in the Hungarian Water Strategy (Kvassay Jenő Plan). On the field of rainwater management of settlements preventive measurements are especially important (both structural and non-structural  measurements). In planning of developments is the realisation of keeping waters locally by building of reservoirs, capable both for protection against damages caused by exceptional floods, cloudbursts and for local retention of water, supporting also welfare- and ecological targets and utilisations – in case they do not repress basic functions of the reservoirs. The aim of this paper is to present non-structural measurements made by the water sector, resp. in case of self-governments to summarise investments in connection with water management and rainwater management of settlements, realised or in progress between 2016 and 2019 and further to formulate proposals for the application of sources in the period of 2021–2027.
Keywords: water management; financing; application period